The Distorted Corporate Capital Structure: Ukrainian Case - Zymovets, Vladyslav; Yershova, Galina; Kornyliuk, Anna; Shynkarenko, Raisa (International Journal of Engineering and Technology, 2018)
Debt and capital are two possible alternative forms of business financing. So the debt and equity ratio shows the choice of management of an enterprise between available financial instruments, taking into account the risk and expected capital expenditures. In this paper the trends in the capital structure of the non-financial corporations in Ukraine are considered. It is argued that the corporate capital structure in Ukraine is distorted. The following specific capital structure features are determined: excessive aggregate NFC indebtedness, excessive share of non-financial debt in total capital, low bank loans’ share in the capital structure (less than 15%), abnormally high small business indebtedness, weak investment activity. We proved that the deepening of the government indebtedness on the background of low monetization level caused structural changes in the financing of business in Ukraine. We also show that the deleverage process caused by the intentional or forced reduction of bank lending was partly compensated by the inflows of capital and loans from offshore companies and shadow economy.